PERAN PUSTAKAWAN SEKOLAH DALAM MENINGKATKAN MINAT BACA DI ERA DIGITALISASI - H. Syamsuddin; Laila Rahmawati (Jurnal IPI (Ikatan Pustakawan Indonesia), 2014)
Librarians as the person who organised a library by way of providing services to people accordance with the duties of the parent institution based on their knowledge through education, required to have competence in the field of library so it mean work accross local, regional, national, international up with digital technology.